2000
DOI: 10.1103/physrevd.62.101701
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of a network of domain walls

Abstract: We explore the idea of a network of defects to live inside a domain wall in models of three real scalar fields, engendering the Z2 × Z3 symmetry. The field that governs the Z2 symmetry generates a domain wall, and entraps the hexagonal network formed by the three-junctions of the model of two scalar fields that describes the remaining Z3 symmetry. If the host domain wall bends to the spherical form, in the thin wall approximation there may appear non-topological structures hosting networks that accept diverse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…[25][26][27][28][29]. We can also consider three-field models, as the ones used in [30][31][32], for instance; this would lead us to other twinlike models.…”
Section: Illustrationmentioning
confidence: 99%
“…[25][26][27][28][29]. We can also consider three-field models, as the ones used in [30][31][32], for instance; this would lead us to other twinlike models.…”
Section: Illustrationmentioning
confidence: 99%
“…[32,33]. Also, it may be of some use in more complex situations, involving three or more scalar fields, in scenarios such as the one where we deal with the entrapment of planar network of defects [34], or with the presence of non-trivial solutions representing orbits that connect vacuum states in the threedimensional configuration space [35].…”
mentioning
confidence: 99%
“…In Ref. [15] the idea of an hexagonal network of defect to be nested inside a topological defect has been investigated in a model described by three real scalar fields. That investigation has shown that when the host domain wall is driven to relax to cylindrical or spherical shape, the nested hexagonal network could give rise to structures resembling nanotubes or fulerenes, respectively.…”
mentioning
confidence: 99%